Merangkul karyawan berorientasi power distance tinggi untuk menampilkan voice behavior: Peranan managerial openness - Rhodes, Puji Gufron; Andiyasari, Andin; Riantoputra, Corina D. (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2021)
This study aims to investigate the moderating role of managerial openness in the relationbetween power distance orientation and voice behavior. We have successfully collected the datathrough online survey with a total of 102 employees in the Organization XYZ Jakarta. Ouranalysis revealed that power distance orientation is negatively related to voice behavior.However, managerial openness weakened the negative relation between power distanceorientation and voice behavior. Thus, managerial openness was a significant moderator of therelationship between power distance orientation and voice behavior. This result supports thesocial exchange theory which assumed that a person’s relationship with other people isdeveloped and evaluated based on the consequences of their behaviors and the efforts exertedin maintaining the relationships. This study contributes to the understanding of the relationshipbetween power distance orientation and managerial openness in constructing voice behavior.